1981
DOI: 10.1111/j.1365-2621.1981.tb04451.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alkaline Protease in Minced Fish on Texture of Heat‐Processed Gels

Abstract: Source of minced fish tissue Measurements of properties relating to the physical integrity of heat-processed fish gels varied among samples obtained over a 1-yr period or subjected to various processing temperatures. Such gel properties correlated well with the heat-stable protease (alkaline protease) activity measured in the raw samples. A significant inhibitor concentration-dependent relationship was noted between the addition of a potato derived protease inhibitor and gel strength. These observations suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 10 publications
2
25
0
Order By: Relevance
“…This is consistent with reports that prolonged heating of fish gels in the 50-70°C range may cause weakening of the gel structure (Makinodan and Ikeda, 1971;Takagi, 1973;Okada et al, 1973;Lee and Toledo, 1976;Lanier et al, 1981). Freezing and thawing further lowered the shear strengths of gels cooked at 60°C to about 50% of their initial value.…”
Section: Results and Discussion Structural Failure Propertiessupporting
confidence: 91%
“…This is consistent with reports that prolonged heating of fish gels in the 50-70°C range may cause weakening of the gel structure (Makinodan and Ikeda, 1971;Takagi, 1973;Okada et al, 1973;Lee and Toledo, 1976;Lanier et al, 1981). Freezing and thawing further lowered the shear strengths of gels cooked at 60°C to about 50% of their initial value.…”
Section: Results and Discussion Structural Failure Propertiessupporting
confidence: 91%
“…2c "-Ie). Therefore, the increase in TCA-soluble material and the breakdown of MHC were possibly due to'a STI-sensitive proteinase(s), probably belonging to the serine proteinase family, as already reported by Lanier et al 9 ) As shown in Table I, 0.5"-11.0 mg STI was apparently enough to inhibit the proteinase(s) contained in 5 g of threadfinbream meat paste. Nevertheless, the strength of gels did not completely recover to that of the control gel, even in the presence of 1 mg of STI (Table I), while the in~en sity of the MHC band recovered to almost the same level as that in the control gel (Fig.…”
Section: S )supporting
confidence: 48%
“…The mechanism causing this is generally poorly understood. Proteolytic activity of alkaline proteases in the muscle has been suggested as the most probable cause of gel weakening in this temperature range (32,33). On the other hand Niwa (34) Miyajima (35) temperatures beyond 58 °C could weaken hydrophobic interactions by destabilizing the hydrogen bonds linking water molecules, which would interfere with hydrophobic hydration.…”
Section: Resultsmentioning
confidence: 97%